Inter-Vivos Transfers and Intergenerational Exchange - Cox, Donald; Rank, Mark R. (The Review of Economics and Statistics, 1992)
The surge of interest in intergenerational transfers in the past decade has sparked a debate over the motivation for them. Are transfers given out of altruism or part of an exchange? While each motive is probably at work to some extent, they know little about whether one motive predominates. The question is relevant for issues concerning public income redistribution and inequality in the family but despite its importance, empirical evidence about motives is scarce because of limited data. They investigate a new data set, the National Survey of Families and Households, which remedies many of the shortcomings of other data sets containing private transfer information. They find that empirical patterns for inter-vivos transfers (i.e., transfers between living persons) are more consistent with exchange than altruism. Copyright 1992 by MIT Press.